Os oficiais do Exército Brasileiro e a formação da elite intelectual sergipana no século XIX : 1822-1889 - Abreu, Ricardo Nascimento (2008)
To understand the way the Brazilian Army officers were trained throughout the XIX century, either through civil and military academies or through their own efforts in pursuing their studies, that involved various fields of knowledge, is the main objective of this study that also intends to analyze the effective participation and contribution of these officers, along with a group of intellectuals from the state of Sergipe, in the political, economical, social, and educational development of this province. By doing so, it intends to dismantle a stereotype that was formed about the referred-to group, a stereotype that this group belongs to a social category of people who lack intellectual qualities. Such affirmation, added to the idea the republicans of the beginning of the XX century passed on to future generations, that during the years of the imperial regime little or nothing was done in the province of Sergipe due to a lack of intellectual values, led to a situation in which few researchers showed interest in studying the 1800 s. Through Jacques Le Goff s concepts of history, added to the sociological interpretations of Norbert Elias, Michel Foucault and Pierre Bourdieu, as well as to the analysis of Jean François Sirinelli, Norberto Bobbio and Sérgio Micelli about the concept of the term intellectual , we can give answers to the hypothesis that were thought of for this research by using as a starting point and as support, the studies of researchers that approached this problem on a national level, people such as the professors José Murilo de Carvalho e Celso Castro, as well as the works of the professors Eugênia Andrade Vieira da Silva e Andreza Santos Cruz, who dealt with the problem on a local level. The necessity of looking for unprecedented sources or the ones that had been little explored forced this research to happen in the depth of the Army Historical Archive, the National Archive, the Collection of the Portuguese Royal Bureau of Reading, the National Library, and in other sites of research that went beyond the limits of the collection of the Historical and Geographical Institute of Sergipe and the Public Collection of Sergipe. This way, we expect to contribute to the motivation and elucidation of the debate regarding the role the military and their institutions had with the other members that made up the social configuration of Sergipe.